PENGARUH LATIHAN RESISTENSE XANDER TERHADAP KECEPATAN TENDANGAN SABIT ATLET PENCAK SILAT PERGURUAN SATRIA MUDA INDONESIA UNIT SMK TARUNA MANDIRI KOTA PEKANBARU - Syahdana, Iqchan; Ramadi, Ramadi; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The research aims to evaluate the impact of xander resistance trainingon the speed of the kick in the high-speed athletes of Satria Young Indonesia SMKTaruna Indigenous Unit of Pekanbaru City. The research method used was a pre-testpost-test design with a total sampling of 16 silat peak athletes. The instrument used is aone-minute stick test. The data is analyzed using the t distribution test with theassumption that if t counts > t tables then there is an influence as suggested on thehypothesis. The results of the study showed a significant increase in the speed of thexander resistance exercise. Statistical analysis showed the t count of 6,310, exceedingthe t value of table 1,753 at the level of significance 0,05, showing a significantinfluence of the Xander resistence exercise on the increased speed of a xander. Inaddition, the normality test of the data showed that the data was distributed normally.Based on these findings, it can be concluded that xander resistance exercisessignificantly influenced the increase in the speed of the stick jump in the athletes of thesilat top. Therefore, xander resistance exercises can be recommended as an effectivemethod to enhance the thruster kicking capability of the silat tops.Keywords: Xander Resistance Exercise, Hard kick